(untitled) (Swiss Medical Weekly, 2012)
OBJECTIVE: Nitric oxide (NO) regulates arterial pressure by modulating peripheral vascular tone and sympathetic vasoconstrictor outflow. NO synthesis is impaired in several major cardiovascular disease states. Loss of NO-induced vasodilator tone and restraint on sympathetic outflow could result in exaggerated pressor responses to mental stress. METHODS: We, therefore, compared the sympathetic (muscle sympathetic nerve activity) and haemodynamic responses to mental stress performed during saline infusion and systemic inhibition of NO-synthase by NG-monomethyl-L-arginine (L-NMMA) infusion. RESULTS: The major finding was that mental stress which during saline infusion increased sympathetic nerve activity by 50 percent and mean arterial pressure by 15 percent had no detectable sympathoexcitatory and pressor effect during L-NMMA infusion. These findings were not related to a generalised impairment of the haemodynamic and/or sympathetic responsiveness by L-NMMA, since the pressor and sympathetic nerve responses to immersion of the hand in ice water were preserved during L-NMMA infusion. CONCLUSION: Mental stress causes pressor and sympathoexcitatory effects in humans that are mediated by NO. These findings are consistent with the new concept that, in contrast to what has been generally assumed, under some circumstances, NO has a blood pressure raising action in vivo.